Regionalism and Catalanism at the University of Valencia (1975-1977) - Aznar i Garcia, Ramon (CIAN-Revista de Historia de las Universidades, 2021)
The article analyzes the different perspectives that a series of university professors adopted between 1975 and 1977 on the Valencian regional / national issue. Most of these academics represented their political organizations in the Taula de Forces Polítiques i Sindicals del País Valencià, an united organization of the democratic opposition constituted in the spring of 1976. Some, in addition, obtained the act of deputy on the occasion of the general elections of June 1977, which ended up being constituents. It is interesting to identify the points of view of these intellectuals, as their considerations influenced —in one sense or another— what was one of the most controversial issues of the democratic transition. In the Valencian case, a vivid identity conflict was also developing and would determine the access to pre-autonomy and —years later— to autonomy itself.